Julinda Abu Nasr - Aghacy, Samira (1997)
When asked by the Institute for Women's Studies in the Arab World to write a tribute to Julinda Abu Nasr on the occasion of her retirement in October, 1997, my mind went back to the short period of time I worked with her as editor of the Al-Raida issue on Women and Literature. In that short span, Julinda stood out as a devoted and inspiring leader of a diverse group of hard working dedicated women.